Childhood or the Pursuit of Solar Acting in Theatre : interview with Guy Freixe - Scalari, Rodrigo; Guy, Guy (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2025)
Guy Freixe—actor, director, theatre researcher, and educator—shares his thoughts on theatre, drawing on his experience as a student at the École Jacques Lecoq and as an actor with the Théâtre du Soleil. The interview explores the approaches of Jacques Copeau, Jacques Lecoq, Philippe Gaulier, and Ariane Mnouchkine, highlighting the importance of the body, movement, and improvisation in their conception of acting. Freixe points out that Lecoq, influenced by the intuitions of Copeau, favours an archaic “memory of the body,” connected to the outside world rather than to a subjective exploration of the actor’s unconscious. This bodily memory is closely linked to childhood, to the instinctive mimicry of the child absorbing and reflecting their environment. In the wake of these reflections, Mnouchkine’s notion of “entering childhood” and the idea of a transgressive childhood in Gaulier’s clown’s craft are also discussed. Freixe leads us to conclude that the appeal to childhood among these artists and educators is, in some way, tied to a search for a playful, light-spirited mode of acting—one that aspires to a radiant, sun-infused theatre.